2021
DOI: 10.21449/ijate.870300
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Formative Assessment Practices on Student Learning: A Meta-Analysis Study

Abstract: The main purpose of this meta-analysis study is to investigate how formative assessment practices promote student learning in Turkey. 32 studies with 47 effect sizes that met the specified criteria such as using true experimental or quasi-experimental design and measuring learning outcomes were included as the final analysis in the meta-analytical review method. The overall mean effect size of the study was obtained as .72 (SE= .07, p< .05). Further investigation through subgroup analysis showed that the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
(42 reference statements)
1
5
0
1
Order By: Relevance
“…In line with its aims and objectives, this study has partly confirmed that regular assessment/formative assessment a positive impact on student learning outcomes with the support of ICT. The results of this study are similar to those of the study by Karaman (2021); Andersson and Palm (2017a). The process enables students to improve their academic achievement through the way teachers support the web-based online systems http://danhgiananglucthpt.edu.vn and http://splearning.vn with online lessons, lesson summaries, videos on key contents of the topics of 8 weeks, and more especially, essay exercises and multiple choice exercises to help students check their results by themselves.…”
Section: Discussionsupporting
confidence: 81%
“…In line with its aims and objectives, this study has partly confirmed that regular assessment/formative assessment a positive impact on student learning outcomes with the support of ICT. The results of this study are similar to those of the study by Karaman (2021); Andersson and Palm (2017a). The process enables students to improve their academic achievement through the way teachers support the web-based online systems http://danhgiananglucthpt.edu.vn and http://splearning.vn with online lessons, lesson summaries, videos on key contents of the topics of 8 weeks, and more especially, essay exercises and multiple choice exercises to help students check their results by themselves.…”
Section: Discussionsupporting
confidence: 81%
“…Prior research has, in general, recognized the role of formative assessment in improving students' learning achievement (Box, 2008; Karaman, 2021; Wang et al., 2004). For instance, Waller (2007) found that more than 70% of the participants agreed that formative assessment triggered changes in classroom teaching strategies in the areas of reading, mathematics and language arts, improving the academic achievement of third‐grade students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many schools and universities are unprepared to accommodate speaking activities and have limited speaking assessments. Several studies found challenges, such as teachers' lack of knowledge in assessing students (Cisse et al, 2021;Gautami & Santosa, 2021;Karaman, 2021;Tapingkae et al, 2020). In this case, teachers should start to use technology as an essential part of education (Nofrion & Wijayanto, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of this research concerns its formative assessment. The formative assessment is an assessment for learning to compute tests and responses in processing employed by the teacher, and students can utilise it in pairs to recognise their capabilities (Fatahhela Dewi et al, 2020;Karaman, 2021). It means that formative assessment analyses, predicts, or examines students' tasks or performance to manage and improve their performance (Tang, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation